It's time for an EU investment promotion agency - José Guimón (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
The author proposes an EU IPA that coordinates FDI promotion and support for foreign investors at a regional level.
Keywords: 330